2006
DOI: 10.4319/lo.2006.51.1_part_2.0639
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the nutrient enrichment of U.S. rivers during the late 20th century and their relation to changes in probable stream trophic conditions

Abstract: We estimated trends in concentrations of total phosphorus (TP) and total nitrogen (TN) and the related change in the probabilities of trophic conditions from 1975 to 1994 at 250 nationally representative riverine monitoring locations in the U.S. with drainage areas larger than about 1,000 km 2 . Statistically significant (p Ͻ 0.05) declines were detected in TP and TN concentrations at 44% and 37% of the monitoring sites, and significant increases were detected at 3% and 9% of the sites, respectively. We used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 31 publications
(38 reference statements)
4
81
1
1
Order By: Relevance
“…McMellor and Underwood (2014) also demonstrated that the reduction in nutrient concentrations in the Colne Estuary (England) between 1980 and 2010 and the abatement in ammonium inputs were due to active interventions in wastewater treatment industry in the catchments. Similar changes have been reported in longterm studies from the Scheldt estuary (Belgium and Netherlands) from the mid-1970s (Soetaert et al, 2006), in the Marsdiep, Helgoland, Odense Fjord, Gulf of Riga systems (Duarte et al, 2009), in Nervio´n in the Basque region of Spain (Borja et al, 2010), and in some US estuaries (Alexander and Smith, 2006;Carstensen et al, 2011).…”
Section: Long-term Observations Of Water Quality For Acknowledging Masupporting
confidence: 61%
“…McMellor and Underwood (2014) also demonstrated that the reduction in nutrient concentrations in the Colne Estuary (England) between 1980 and 2010 and the abatement in ammonium inputs were due to active interventions in wastewater treatment industry in the catchments. Similar changes have been reported in longterm studies from the Scheldt estuary (Belgium and Netherlands) from the mid-1970s (Soetaert et al, 2006), in the Marsdiep, Helgoland, Odense Fjord, Gulf of Riga systems (Duarte et al, 2009), in Nervio´n in the Basque region of Spain (Borja et al, 2010), and in some US estuaries (Alexander and Smith, 2006;Carstensen et al, 2011).…”
Section: Long-term Observations Of Water Quality For Acknowledging Masupporting
confidence: 61%
“…Upward overall trend 1972 1974 1976 1978 1980 1982 1984 1986 1988 1990 1992 1994 1996 1998 2000 2002 2004 2006 The trends in nutrient concentrations in U.S. streams between 1993 and 2003 are notably different than those between 1975 and 1994, when more downward trends in nutrient concentrations occurred (Alexander and Smith, 2006). In some U.S. streams, improvements in water quality realized after enactment of the Clean Water Act of 1972 have been offset somewhat by the effects of more recent changes in climate, population, land use, or agricultural and industrial activities.…”
Section: Downward Overall Trend Criterion Not Reachedmentioning
confidence: 90%
“…Eutrophication has long been a major focus of limnology and marine research (Vollenweider 1968;Hutchinson 1969;Likens 1972), but has gained in prominence in recent decades as anthropogenic modification of the landscape continues (Smetacek et al 1991;Nixon 1995;Jordan et al 1997;Howarth et al 2000;Rabalais et al 2001;Boyer et al 2002;Kemp et al 2005;Alexander and Smith 2006). Human activities, such as agriculture and urban development, have been linked to increases in nutrient and sediment loading (Correll 1987;Turner and Rabalais 1991;Carpenter et al 1998) and can adversely affect water quality, productivity, and trophic structure (Ryding and Rast 1989;Rekolainen et al 1995;Rast and Thornton 1996) in receiving lakes, wetlands, estuaries, and coastal waters (Orth and Moore 1983;Officer et al 1984;Jordan et al 1991a, b;Frink 1991;Golterman 1995;Howarth et al 1996;Vukadin et al 1996;Carpenter et al 1998;Boesch et al 2001).…”
Section: Introductionmentioning
confidence: 99%